The complete guide to backpacking : field-tested gear, advice, and know-how for the trail. (Falcon, 2017)
The Complete Guide to Backpacking combines and distills the most useful and relevant skills necessary for backpacking in one guide, from Backpacker magazine. From detailed descriptions of what to pack and how to pack it, to navigation and campsite cooking, to managing outdoor hazards and more, The Complete Guide to Backpacking is the resource for Backpacking-related know-how.